Zu aktuellen Tendenzen des Kommentierens in der polnischen Presselandschaft - Mac, Agnieszka (Stylistyka, 2019)
The article focusses on commentary as a text genre in the daily press. The aim of the first part is to present the prototypical marks and characteristic differences of the genre as well as its conditions. The second part discusses possible ways of broadening the genre pattern on the basis of the analysed samples from the daily press of different ranges: newspapers of nationwide, regional, and local range according to selected criteria. The article strives to answer the question about the form of the contemporary press commentary. It also attempts to explain the reasons why journalists tend to depart from the pattern of the genre.